Conciencia tributaria y cumplimiento de obligaciones tributarias de los microempresarios del Mercado Municipal de Requena 2022 - Valles Zambrano, Edilberto Raul (2023)
The study objective of the report was to determine the relationship between tax awareness and compliance with tax obligations of micro-entrepreneurs in the Requena 2022 Municipal market, where an applied study and non-experimental design was chosen, taking 51 businessmen as a sample. , to whom a questionnaire was applied to collect information. Obtaining as results that the level of tax awareness is medium (31%), because they have information on current tax regulations and includes the payment of their taxes as a contribution to society; In addition, they pay before the date to avoid being declared delinquent. For its part, the level of compliance with tax obligations is medium (27%), since most of them know the payment schedule for the sales declaration, but at the same time they have already received tax sanctions from SUNAT. Coming to determine that there is an important relationship between the variables, according to the results of a study with a correlation coefficient of 0.791.